2022
DOI: 10.4103/indianjpsychiatry.indianjpsychiatry_484_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium metabolism in ADHD: The relationship between parathyroid hormone and ADHD symptom severity

Abstract: Background: Vitamin D has been found to be associated with the pathogenesis of attention deficit hyperactivity disorder (ADHD). However, the potential role of parathyroid hormone (PTH) is still unclear. Aim: We aimed to investigate the association between calcium metabolism and ADHD symptomatology. Methods: We included 106 participants aged between 7 and 13 years old (51 ADHD patients, mean age: 9.54 ± 1.77, 55 healthy controls mean age: 9.97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These findings suggest that calcium dysregulation in the brain may influence impulsivity. This claim is further supported by Altun Varmis et al , who found that increased calcium levels were associated with ADHD, as were reduced parathyroid hormone levels, which helps regulate calcium levels [ 57 ]. In a childhood ADHD EWAS conducted by Mooney et al , the top-ranked differentially methylated position, showing increased DNAm in ADHD cases compared with non-ADHD controls, was located in the promotor region of SLC7A8 [ 6 ].…”
Section: Discussionmentioning
confidence: 76%
“…These findings suggest that calcium dysregulation in the brain may influence impulsivity. This claim is further supported by Altun Varmis et al , who found that increased calcium levels were associated with ADHD, as were reduced parathyroid hormone levels, which helps regulate calcium levels [ 57 ]. In a childhood ADHD EWAS conducted by Mooney et al , the top-ranked differentially methylated position, showing increased DNAm in ADHD cases compared with non-ADHD controls, was located in the promotor region of SLC7A8 [ 6 ].…”
Section: Discussionmentioning
confidence: 76%
“…113 The relationship between calcium metabolism and the symptoms of ADHD was also the subject of another study by Varmis ¸and his Colleagues. 114 Total 106 participants between the ages of 7 and 13 were included in this study. Vitamin D, PTH, calcium, magnesium, phosphorus, and alkaline phosphatase (ALP) levels were assessed using blood samples.…”
Section: Maternal Age and Risk Of Adhdmentioning
confidence: 99%
“…PTH and CTRS hyperactivity, CGI-RI and CGI-EL sub-scores, CGI-Total, DSM-IV-Inattention, DSM-IV Hyperactivity/ Impulsivity, and DSM-IV-Total scores all showed a negative connection. 114 Furthermore, various findings revealed an association between the maternal Vitamin D level and ADHD in children (Table 1).…”
Section: Maternal Age and Risk Of Adhdmentioning
confidence: 99%